2002
DOI: 10.1080/078538902321117751
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of erbB2 positivity for evaluation of high-risk patients

Abstract: The most obvious patients for primary trastuzumab therapy in breast cancer are N+ patients with high erbB2 immunostaining index (> 1.5) and bcl-2 negative immunostaining. In our material 2% of all breast cancer patients fell in this category. This patient group should be selected for testing trastuzumab in the primary treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several studies have correlated the overexpression of the HER2/neu oncogene with poor prognosis in breast cancer patients [10,11], and demonstrated that evaluating HER2/neu protein by immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), and chromogenic in situ hybridization (CISH) are important in selecting optimal therapy and predicting prognosis in breast cancer patients [12-14]. Slamon et al and Jalava et al [15,16], showed that intensive HER2/neu immunostaining was a highly significant negative prognosticator in LN+ patients (especially postmenopausal), but not a significant prognosticator among LN- patients or patients younger than 52 years. The paper of Jalava et al [16] suggested that the size of the patient group which absolutely seemed to need the targeted therapy against the amplified HER2/neu receptor was at least 2% of all breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have correlated the overexpression of the HER2/neu oncogene with poor prognosis in breast cancer patients [10,11], and demonstrated that evaluating HER2/neu protein by immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), and chromogenic in situ hybridization (CISH) are important in selecting optimal therapy and predicting prognosis in breast cancer patients [12-14]. Slamon et al and Jalava et al [15,16], showed that intensive HER2/neu immunostaining was a highly significant negative prognosticator in LN+ patients (especially postmenopausal), but not a significant prognosticator among LN- patients or patients younger than 52 years. The paper of Jalava et al [16] suggested that the size of the patient group which absolutely seemed to need the targeted therapy against the amplified HER2/neu receptor was at least 2% of all breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Slamon et al and Jalava et al [15,16], showed that intensive HER2/neu immunostaining was a highly significant negative prognosticator in LN+ patients (especially postmenopausal), but not a significant prognosticator among LN- patients or patients younger than 52 years. The paper of Jalava et al [16] suggested that the size of the patient group which absolutely seemed to need the targeted therapy against the amplified HER2/neu receptor was at least 2% of all breast cancer patients. Press et al [17], however, suggested that HER2/neu is a significant prognosticator in LN- patients.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study show that breast cancer is diagnosed in younger age groups (46 years), in more advanced stages, with features of aggressive behavior. Carcinomas with HER2 abnormalities are often associated with more aggressive features, such as high grade tumours, lymph node involvement, and a higher rate of disease recurrence and mortality [11,18,19]. In the pre-mor stage (p < 0.0001), larger tumor size (p = 0.0001) and higher grade (p = 0.001), as well as those with systemic metastasis (p < 0.0001) (Figure 3).…”
Section: Survival Analysismentioning
confidence: 99%
“…HER2 protein over-expression is also of great importance to guide hormone therapy, predicting approximately 50-75% of response rate to hormone therapy. HER2 protein is usually used as an eligibility criterion for anti-HER2 therapy, such as trastuzumab, which has been shown to be an effective treatment for HER2-positive breast cancer, even in advanced stages [11].…”
Section: Introductionmentioning
confidence: 99%